Childhood obesity: An approach to individualized treatment - Collins, Philip; Brolis, Nils (Osteopathic Family Physician, 2022)
In the United States, obesity prevalence has surpassed alarming rates and reached epidemic proportions with increased body mass index and poor diet being among the top causes of morbidity and mortality. Approximately 18.5% of children in the United States have obesity. Childhood obesity is associated with medical conditions such as cardiovascular disease, type 2 diabetes mellitus, asthma and musculoskeletal disorders among other conditions. It is also associated with an increased risk for discrimination and bullying. The goal of treatment in the pediatric and adolescent patient with overweight or obesity is to develop healthy habits and lifestyle patterns which will hopefully persist into adulthood in order to prevent future adverse health outcomes, improve quality of life and improve body image and self-esteem. Osteopathic family physicians are well suited to provide the needed comprehensive care, taking a holistic, patient-centered treatment approach including nutrition, activity and behavior. While therapeutic lifestyle changes are the primary focus of treatment, the provider must also consider socioeconomic factors, mental health, treatment of comorbidities and familial factors when determining treatment. This article aims to summarize the risks and consequences of childhood obesity as well as outline the approach the osteopathic family physician can take to assessment and treatment of the pediatric patient with obesity.